A impulsividade dos portadores de transtorno bipolar resulta em alta prevalência de comorbidade com transtornos do controle dos impulsos? - Caetano, Murilo Ferreira (2016)
Introduction: Bipolar disorder (BD) is a chronic and potentially harmful psychiatric condition that usually begins in adolescence or in early adulthood. It is associated with suicidal behavior, social and occupational impairment, distress, substance abuse, low quality of life and high prevalence of comorbid psychiatric disorders. Impulsivity is a marked feature of the acute phases but has been showed to be also a longitudinal feature of the the disorder, a trait. Impulse control disorders (ICD) form a heterogeneous group with several syndromes characterized by impulsive and compulsive behavior leading to marked distress and social or occupational impairment. ICD have been associated with both depressive and anxiety disorders and substance abuse, its relation with BD is yet to be understood. Methods: We evaluated 42 patients with BP I and BP II disorders according to DSM-IVTR criteria. The diagnosis was confirmed using the Structured Clinical Interview for Axis I disorders of the DSM-IV (SCID-I-P). Sociodemographic data were assessed using the Brazilian Bipolar Disorder Association standard interview. ICD were assessed with a specific SCID module for ICD. Impulsivity was measured using the Barrat Impulsiveness Scale (BIS-11). Patients with severe depression (MADRS > 34) or with manic symptoms (Young >6) were excluded to avoid difficulties in data collection. Patients with active or a sequel of neurological disorders (such as Epilepsy, Parkinson Disease and Stroke) were excluded because it has been associated with impulsive behavior. We compared the group with at least one ICD with the group without ICD in terms of impulsivity, sociodemographic data, comorbities and course of the disease. Results: The prevalence of ICD was 35.7 % (n=15). Compulsive buying and intermittent explosive disorder were the most commons followed by skin picking disorder, trichotilomania, kleptomania and internet addiction. There were no cases of gambling disorder or pyromania. The ICD+ group was found to have more men, co-morbidity with alcohol abuse, early onset of the first depressive episode, less hospital admissions due to mania and the subjects were more likely to be using antidepressants. There was no difference regarding the age, type of BD, comorbidity with anxiety or eating disorders, psychotic features, age of first manic episode, educational level, marital status or income. Impulsivity measured by BIS-11 was higher in the ICD+ group, as well as the inhibitory control scale of the BIS-11. No difference was found in ‘lack of planning’ domain of the BIS-11. Conclusion: ICD are very common in BD and should always be assessed in clinical setting. Alcohol abuse, masculine sex, early onset of the first depressive episode and fewer hospital admissions to treat mania were associated with comorbid ICD.